EXPERIENCE OF USING DIGITAL SYSTEMS FOR DIAGNOSTICS OF HYPERTROPHIC SKIN SCARS OF FACE - D.S. Avetikov; O.P. Bukhanchenko; I.O. Ivanytsky; N.A. Sokolova; I.V. Boyko (Ukrainian Medical Stomatological Academy, 2018)
The relevance of the problem. Head and neck scars resulting from the effects of various endogenous and exogenous factors are an actual problem of modern surgical stomatology. A large number of scientific researches devoted to the study of different methods of diagnosis of head and neck scars indicates that the verification of the diagnosis is a highly complicated issue. Currently, conventional algorithms for selecting methods of treating patients with scars are available. The development of such algorithm is difficult due to the uncertainty of criteria for the differential diagnosis of various types of scars. Despite significant pathogenetic and morphological differences of scarring, some of their types often have clinically similar features, resulting in a significant number of diagnostic errors. In its turn, carrying out the treatment without taking into account the clinical and morphological structure of scars usually leads to the lack of tangible therapeutic effect, recurrence and increased growth of scar tissue. That is why the development of a clear algorithm of comprehensive examination of this category of patients is of particular importance for determining the tactics of their treatment. The aim of the research is to increase the effectiveness of face scars treatment due to identification of type of scar-modified tissue by means of method of digital visualization of graphic digital images. Objects and methods of the research. Fifty patients with hypertrophic scars of face were examined. Further analysis of the structure of hypertrophic scars was performed using RGB-method of visualisation. At present, computer digital image research is widely used in histological, cytological, pathologic and immunological studies, which led us to consider the use of digital analysis of images as the initial stage of primary diagnosis in various types of postoperative scarred facial tissues. Computer imaging is still the only source for obtaining visualized qualitative and quantitative information and preserving it in digital form. Results of the research. We have studied the distribution of color constants of red, green and blue colors in 4 points: T1 - the area of intact skin, T2 - the medial and T3 - the lateral edge of the scar, and T4 - the area of the middle zone of scar. Due to the proposed method, the features of architectonic layers of the skin in the area of hypertrophic scar have been studied in detail. The obtained results allow improving the differential diagnosis of scars and expanding the possibilities to develop the pathogenetically grounded treatment of patients with head and neck scars. The analysis of the results of digital visualization of graphic digital images showed that statistically reliable differences in digital indices, being observed during visualization of hypertrophic scars, could be an important criterion of their differential diagnostics. Conclusion. Thus, examination of patients with scars of the maxillofacial region, providing the RGB-method, is an effective method of non-invasive diagnosis of hypertrophic scars allowing to evaluate the changes in scar-modified tissues in dynamics. The authors substantiated the feasibility of the use of RGB-system for the improvement of differential diagnosis of hypertrophic scars of the head and neck. Due to the proposed method, features of architectonic layers of the skin in the area of hypertrophic scar have been studied in detail. The obtained results allow to improve the differential diagnosis of scars and expand the possibilities of developing pathogenetically grounded treatment of patients with scarring of the head and neck.